Histopathological study of effects phenobarbital in Goats - Zainab W. K; Hanan Ali; Samera Abd Al-zahra (Kufa Journal for Veterinary Medical Sciences, 2018)
In this data was done to demonstrate the administration of phenobarbital compounds & showed histopathological effects. In this study fourteen of local goats were divided into two groups (each group seven animals) for 60 days. First one were treated phenobarbital injected with 35 mg \kg.B.W.,twice daily ,second group act as control group. These animals were examined internally and externally during adaptation period. After end experimental period scarified the animals, necropsy, preparation of slid by routine technique  and examined by light microscope, there are showed different histological changes into tissue of animals treatment with phenobarbital such as degeneration of epithelial cells lining of renal tubules of kidney and thyroid gland congested of central vein with fibrosis in liver ,vacuolated of mucosal layer of rumen, small intestine and pancreas, atrophyseminiferous tubules of testis and lymph node.